Psichoterapijos istorijos: pykčio raiškos ir dinamikos refleksijos - Lozovska, Juliana; Gudaitė, Gražina (Psichoterapijos veiksmingumas: terapiniai veiksniai ir subjektyviai išgyvenami pokyčiai, 2014)
Anger, its development, differentiation, expression and control are important themes in psychotherapy process. Psychotherapists have developed different hypotheses about anger dynamics and have related it to effectiveness of psychotherapy. The study explores a subjective experience of long-term psychotherapy process. Seven women with experience in analytical, psychodynamic or existential therapy participated in our research. We asked clients to tell the story of their psychotherapy with special focus on the most important moments of the process. The method of thematic analysis was used in the qualitative analysis of data. Psychotherapeutic stories revealed various aspects of therapeutic experience, including the theme of anger. Respondents reflected on their therapeutic experience, spontaneously mentioned important changes in anger, such as reduction of its intensity, feeling of relief and liberation. Changes in anger were linked to the possibility of experiencing and expressing anger in psychotherapy, exploring anger’s motives, and experimenting with different forms of anger expression. Respondents claimed it was important to express their anger reactions towards therapists directly and to explore its meaning. Many respondents highlighted the role of the therapist in the process of exploration of anger. Analysis of respondents’ reflections showed that successful work with anger could be considered as a criterion of effective psychotherapy.